The green formulation of silver nanoparticles for the anticancer and lupus nephritis treatment applications and reducing the inflammatory cytokines in the rat periodontal model - Yan Sun; Qingfei Yu (Journal of Science: Advanced Materials and Devices)
In this study, a novel bio-inspired synthesis for the preparation of Ag NPs by Calendula persica flower extract has been researched. Also, the effects of the recent composite on lupus nephritis by following the TGF-β1 signaling pathway in mice and gingival amounts of IL1-β and TNF-α in the animal periodontal model were determined. To assess the crystal nature, morphology and size of the prepared nanoparticles, X-ray diffraction (XRD), transmission electron microscopy (TEM), ultraviolet–visible (UV–Vis) and field emission-scanning electron microscopy (FE-SEM) analyses were applied in this study. The prepared Ag NPs was employed for its effectiveness against colon cancer cell line (C26). The bio-synthesized Ag NPs had also cytotoxic property versus colon cancer based on MTT protocol. Collectively, the Ag NPs fabricated by biological way has potential applications in inflammatory treatment. In lupus nephritis section, indexes in animal tissues and serum were identified using specific kits, while pathological alterations in the mice kidney were examined through H&E staining. Additionally, qPCR was employed to determine the expression related to TGF-β 1 in kidney, thereby providing further insight into the silver nanoparticles mechanism. The findings indicated that silver nanoparticles reduced the mRNA expression levels of TGF-β 1 and NF-κB in the kidneys, while simultaneously increasing the Mn-SOD and IκB-α expression. Histological examination of H&E-stained sections revealed that silver nanoparticles mitigated the morphological abnormalities of the glomeruli and the inflammatory infiltration associated with nephritis. Silver nanoparticles demonstrated an inhibitory effect on the dsDNA positive rate in animal suffering from nephritis. Silver nanoparticles were found to reduce the increase in urinary protein and the pro-inflammatory cytokines concentrations in both the kidney and serum. In the periodontal model study, 0–3 ligatures were applied to induce the inflammatory periodontitis in right mandibular first molar neck in rats. The levels of inflammatory cytokines (IL1-β, CINC-1, IL-10 and TNF-α) were determined by common immunological test, ELISA. The findings revealed that Ag NPs administration could decease the IL1-β and TNF-α production in the rat periodontal model gum tissue. In addition, the outcome of this research indicated that IL1-β and TNF-α levels raised in the rat periodontal model gum tissue compared to control group. Ag NPs increased the levels of superoxide dismutase, catalase, and plasma bone alkaline phosphatase and reduced the IL1-β, TNF-α, inducible nitric oxide synthase and RANK genes mRNA expression. The results indicate that pre/post-treatment with Ag NPs because of its direct activity on pro-inflammatory cytokines inhibition improved the inflammatory symptoms in the periodontitis and lupus nephritis animals.